# Haskell Quiz/Constraint Processing/Solution Jethr0

### From HaskellWiki

m (added version which doesn't use builtin List Monad) |
(sharpen cat) |
||

(3 intermediate revisions by one user not shown) | |||

Line 1: | Line 1: | ||

− | [[Category:Code]] |
+ | [[Category:Haskell Quiz solutions|Constraint Processing]] |

Basically there's nothing to be done in haskell for this quiz. |
Basically there's nothing to be done in haskell for this quiz. |
||

Line 37: | Line 37: | ||

<haskell> |
<haskell> |
||

− | data List a = List a (List a) | Empty deriving (Show) |
+ | data List a = a ::: (List a) | Empty deriving (Show) |

− | |||

− | appendL :: List a -> List a -> List a |
||

− | appendL Empty ys = ys |
||

− | appendL (List x xs) ys = x `List` appendL xs ys |
||

foldrL :: (a->b->b) -> b -> List a -> b |
foldrL :: (a->b->b) -> b -> List a -> b |
||

foldrL _ start Empty = start |
foldrL _ start Empty = start |
||

− | foldrL f start (List x xs) = f x (foldrL f start xs) |
+ | foldrL f start (x ::: xs) = f x (foldrL f start xs) |

+ | |||

+ | appendL :: List a -> List a -> List a |
||

+ | appendL xs ys = foldrL (:::) ys xs |
||

concatL :: List (List a) -> List a |
concatL :: List (List a) -> List a |
||

Line 47: | Line 47: | ||

instance Functor List where |
instance Functor List where |
||

− | fmap f = foldrL (\a b -> f a `List` b) Empty |
+ | fmap f = foldrL (\a b -> f a ::: b) Empty |

instance Monad List where |
instance Monad List where |
||

− | return x = List x Empty |
+ | return x = x ::: Empty |

l >>= f = concatL . fmap f $ l |
l >>= f = concatL . fmap f $ l |
||

Line 59: | Line 59: | ||

range :: (Integral a) => a -> a -> List a |
range :: (Integral a) => a -> a -> List a |
||

range from to | from > to = Empty |
range from to | from > to = Empty |
||

− | | from == to = List to Empty |
+ | | from == to = to ::: Empty |

− | | otherwise = List from (range (from+1) to) |
+ | | otherwise = from ::: range (from+1) to |

constr' = do a <- range 0 4 |
constr' = do a <- range 0 4 |

## Latest revision as of 10:45, 13 January 2007

Basically there's nothing to be done in haskell for this quiz.

As the List Monad already provides non-deterministic evaluation with "guard" as a description of constraints, you really just have to write the problem in the List Monad and be done with it.

Of course one could write all kinds of wrapping hackery, but I think from the standpoint of usability and conciseness the built-in behaviour of haskell is already pretty optimal.

constr = do a <- [0..4] b <- [0..4] c <- [0..4] guard (a < b) guard (a + b == c) return ("a:",a,"b:",b,"c:",c) {- > constr [("a:",0,"b:",1,"c:",1) ,("a:",0,"b:",2,"c:",2) ,("a:",0,"b:",3,"c:",3) ,("a:",0,"b:",4,"c:",4) ,("a:",1,"b:",2,"c:",3) ,("a:",1,"b:",3,"c:",4)] -}

Obviously, solving a problem with built-in functionality always feels a little like cheating, because it's "pure chance" that the solution to the problem is already built-in.

So, for the sake of argument and because I was bored here's the same solution under the premise that haskell's List Monad didn't already exist.

Unfortunately I "had" to reimplement a fair bit of the Prelude, but that's what happens if you start creating unrealistic scenarios :). Of course, the "do" notation is also kind of a built-in, but representing it with bind (>>=) only made is less nice to look at.

data List a = a ::: (List a) | Empty deriving (Show) foldrL :: (a->b->b) -> b -> List a -> b foldrL _ start Empty = start foldrL f start (x ::: xs) = f x (foldrL f start xs) appendL :: List a -> List a -> List a appendL xs ys = foldrL (:::) ys xs concatL :: List (List a) -> List a concatL = foldrL appendL Empty instance Functor List where fmap f = foldrL (\a b -> f a ::: b) Empty instance Monad List where return x = x ::: Empty l >>= f = concatL . fmap f $ l instance MonadPlus List where mzero = Empty mplus = appendL range :: (Integral a) => a -> a -> List a range from to | from > to = Empty | from == to = to ::: Empty | otherwise = from ::: range (from+1) to constr' = do a <- range 0 4 b <- range 0 4 c <- range 0 4 guard (a < b) guard (a + b == c) return (a,b,c)